Corelation Between Husband’s Support With Maternal Self-Efficacy in Pekanbaru - Siska Helina; Yanti Yanti; Elly Susilawati (Journal of Midwifery, 2019)
The importance of breastfeeding for the health of mothers and children has been accepted by people all over the world. Based on data from the Pekanbaru City Health Office (2016), the coverage of exclusive breastfeeding in Pekanbaru was 50.70%, below the national target of 80% and in the Umban Sari Health Center was only 39.22%. Some studies stated that self-efficacy and husband's engagement during the breastfeeding process support the successful of breastfeeding. The purpose of this study is to determine the correlation between husband's support and maternal self-efficacy in breastfeeding. This is a non-experimental research with correlational type. The study was conducted at the Umban Sari Health Center in January to September 2019. The data was collected by using primary data by self-reported questionnaire, processed by editing, coding, entry, cleaning processing, and then analyzed by regression correlation test. The results showed that there is a strong correlation between emotional (r = 0.63), informational (r = 0.56), appraisal (r = 0.53) support with maternal self-efficacy in breastfeeding, but moderate correlation for instrumental support (r = 0.47). By these results, it is suggested that the breastfeeding class program in the prenatal by involving husband needs to be held